Approaches To the Digital Transformation of Traditional Business Processes. - Oleksandr Ieselev (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2025)
The article provides a detailed account of approaches applied to the digital transformation of traditional business processes. In the context of a rapid technological shift, such transformations become indispensable for the survival and competitiveness of economic actors. However, despite a proliferation of publications, both academic and practitioner literature remain fragmented in their definitions of the nature of transformational steps, their scope, and the organizational mechanisms involved. The objective of this paper is to undertake a critical analysis of the conceptual foundations of digital transformation and to identify the primary directions that underpin the rethinking and reconfiguration of established operational models. Special attention is given to juxtaposing strategic, institutional, and industry‐applied approaches, as well as to exploring the tensions between normative rhetoric and the empirical feasibility of these changes. A typology of the approaches under review is presented, key limitations and barriers are delineated, and the author’s position on the novelty of processes for the digital reconfiguration of business architecture is articulated. The scientific and practical value of this work lies in systematizing diverse viewpoints on the topic and interpreting them through an interdisciplinary lens. The material set forth will be of use to scholars in management, digital economics, organizational theory, and applied informatics, as well as to consulting professionals and business architects engaged in facilitating digital transformations.